(untitled) - D Greboval (Rome, 1994)
This is a review of the characteristics of the fisheries of the shared lakes of the Rift Valley in Eastern Africa. The first section provides a general overview of inland fisheries in the region, with the focus on basic fisheries and socio-economic indicators. The second section provides more specific infomation on fisheries on a lake-by-lake basic. Emphasis is on graphic presentation and brief analyses of current and historical information on catch and fishing effort. Finally, in the third section complementary country-level socio-economic data are presented for the 11 countries concerned.
Keywords: fisheries